Tourism behaviour : travellers' decisions and actions - March, Roger (CAB books., 2005)
This book focuses on individuals' and households' thinking and behaviour relating to discretionary travel. Part I (chapters 1-3) covers new theories of tourism behaviour and offers examples of empirical examinations of these theories in three settings: Australia, Hawaii (USA), and Prince Edward Island (Canada). Part II (chapters 4-11) builds and examines a theory comparing leisure traveller plans and behaviour. The eight chapters in part II cover all four possible behaviours: (1) planned and done (deliberate strategies); (2) planned and not done (unrealized strategies); (3) unplanned and done (emergent strategies); and (4) unplanned and not done (unused but possible strategies). The trade-offs made in life among work, leisure, travel and personal maintenance actions and how plans actually relate to deeds are therefore considered. Plans and behaviours for tourist spending, length of stay, attractions, destinations, accommodation and activities are reviewed and how marketing strategies affect consumer plans are investigated. This book is intended for travel and leisure researchers, destination marketing managers and advanced students in tourism and consumer behaviour. The book has a subject index.